Are allergen batch differences and the use of double skin prick test important? - Thomsen, Gert F (BMC Pulm Med, 2015)
BACKGROUND: Skin prick tests (SPT) are widely used both in clinical diagnostics and in research. The standardization of allergen extracts is well documented to be crucial for the validity of SPT, whereas less emphasis has been placed on reproducibility and the SPT procedure itself. The objectives of this study are to clarify how the double skin prick test procedure influence the sensitivity and specificity of the test and to analyse the differences in weal size in skin prick tests between two batches of allergen extracts from the same vendor. METHODS: The association between rhinitis and SPT was assessed among 1135 persons from a general population sample. SPT was performed twice with 10 common aeroallergens. In a subsample of 90 persons SPT was performed simultaneously with five of the allergens using different batches. RESULTS: Thirty percent had at least one positive SPT. Among asthmatics this number was 62%. Only minor differences were seen between the sizes of two weals from the same batch. A second SPT with the same batch did not change the association between rhinitis and sensitization. When performing SPT with two different batches disagreement was observed in 2% (Birch) to 11% (Cat) of the subjects. CONCLUSIONS: Performing SPT twice with the same allergen batch does not enhance the validity of the test, and value of double testing can be questioned. Considerable differences in SPT response with different batches from the same manufacturer were observed. Thus inter batch differences in allergen extracts might be a source of variability.